2020
DOI: 10.1038/s42003-020-1089-8
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitous flavonoid quercetin is an atypical KCNQ potassium channel activator

Abstract: Many commonly consumed plants are used as folk medicines, often with unclear molecular mechanisms. Recent studies uncovered the ubiquitous and influential KCNQ family of voltage-gated potassium (Kv) channels as a therapeutic target for several medicinal plant compounds. Capers - immature flower buds of Capparis spinosa - have been consumed for food and medicinal purposes for millennia. Here, we show that caper extract hyperpolarizes cells expressing KCNQ1 or KCNQ2/3 Kv channels. Capers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…We previously found that quercetin enhances both activation and inactivation of homomeric KCNQ1 channels, inducing visible voltage-dependent decay at depolarized potentials (Redford and Abbott, 2020), recapitulated here (Figure 9F). We applied a combination of tannic acid and quercetin to KCNQ1 and found that the combination was not as effective as tannic acid alone in inducing constitutive current, but the current at less hyperpolarized potentials was inhibited more effectively than for either compound alone.…”
Section: Tannic Acid Exerts Kcne-dependent Effects On Kcnq1 Channel Activitysupporting
confidence: 84%
See 3 more Smart Citations
“…We previously found that quercetin enhances both activation and inactivation of homomeric KCNQ1 channels, inducing visible voltage-dependent decay at depolarized potentials (Redford and Abbott, 2020), recapitulated here (Figure 9F). We applied a combination of tannic acid and quercetin to KCNQ1 and found that the combination was not as effective as tannic acid alone in inducing constitutive current, but the current at less hyperpolarized potentials was inhibited more effectively than for either compound alone.…”
Section: Tannic Acid Exerts Kcne-dependent Effects On Kcnq1 Channel Activitysupporting
confidence: 84%
“…The five plants most effective at negative-shifting KCNQ2/3 activation V 0.5 were A. menziesii , A. glandulosa , U. dioica, P. munitum , and H. maximum ( Figure 3D ). Prior analyses of A. menziesii and other Arbutus species leaf extracts ( Kabadi and Hammarlund, 1963 ; Kouki and Manetas, 2002 ; Zitouni et al, 2020a , b ) revealed tannic acid as a principal component, together with compounds related to quercetin, which we previously found to activate KCNQ2/3 ( Redford and Abbott, 2020 ) (quercetrin, quercetin 3-β- D -glucoside and quercetin 3-O-α- L -arabinopyranoside), gallic acid, and avicularin. In addition, the glycosylated hydroquinone arbutin has been identified as the major abundant bioactive component in leaves of closely related Arbutus unedo ( Kabadi and Hammarlund, 1963 ; Tenuta et al, 2019 ).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Because it seemed unlikely that GTE was inducing inactivation in a non-inactivating channel [ 30 ], we next investigated the impact GTE had on endogenous oocyte currents ( Fig. 1J ).…”
Section: Resultsmentioning
confidence: 99%